1293. The Next Step in PrEP: Evaluating Outcomes of a Pharmacist-Run HIV Pre-Exposure Prophylaxis (PrEP) Clinic. (26th November 2018) - Ryan, Keenan; Lewis, Jessica; Sanchez, Daniel; Anderson, Beverly; Mercier, Renee-Claude
Abstract: Background: PrEP has been proven as an effective option for preventing the transmission of HIV; however, there are limited numbers of providers willing to prescribe PrEP. Pharmacists are an underutilized resource that are able to provide PrEPservices in many states. In Albuquerque, New Mexico, one of the nation's first pharmacy-run HIV PrEP clinics was established in July 2015. The objective of this study was to describe the outcomes of an alternative model for HIV prevention. Methods: The electronic medical record was used to identify and retrospectively review patients of the PrEP clinic from July 2015 to July 2017. Pertinent information including: risk factors for HIV acquisition, sexually transmitted infections (STIs) history, laboratory and medication-related data were captured. Data on partner HIV status and HAART regimen was collected when available. Adherence was evaluated by self-reported missed doses and the compliance rate was calculated from the patient's medication fill history. Descriptive statistics was performed using SPSS. Results: The first PrEP appointment was attended by 136 patients during study period. Baseline demographics are reported in Table 1. Two patients tested positive for HIV at baseline. PrEP was started in 127 patients with tenofovir/emtricitabine(TDF/FTC). There were no HIV seroconversions among those who started PrEP. Only one patient discontinued due to side effects. No significant elevation in Scr was noted over time. Overall, patients demonstrated a high adherence rate with an average of <1 missed doses per month and a median compliance rate of 0.99. Conclusion: A pharmacist run PrEP clinic is an alternative model to increase patient access to PrEP. TDF/FTC was provided to high-risk individuals and well-tolerated. Providers were able to promote high level of adherence. Disclosures: All authors: No reported disclosures.